Processo inovativo agroindustrial no Centro-Oeste com base na teoria evolucionária - Pereira, Rhafael Secundino Hipólito (2019)
This paper aims to investigate the innovative efforts of companies in the Midwest region in the period from 2009 to 2011. It was intended to observe how companies in the Midwest region that comprise (Goiás, Mato Grosso and Mato Grosso of the South) are behaving in relation to the question of innovation and what is the participation of the impact of these firms in relation to results at the national level. Within the evolutionary perspective The result found reveals that companies in general have weak innovative activities and with that little technical advance. As a consequence, the region’s economic growth process can be compromised since the innovation variable is extremely important for a region to present sustained growth.